'It was daunting. I was 18 and I left residential care and there was no support whatsoever': a scoping study into the transition from out-of-home-care process in Tasmania, Australia. (26th December 2020) - O'Donnell, Renée; MacRae, Ann; Savaglio, Melissa; Vicary, Dave; Green (nee Cox), Rachael; Mendes, Philip; Kerridge, Gary; Currie, Graeme; Diamond, Susan; Skouteris, Helen
Abstract: Young people who leave Out-of-Home Care (OoHC) are a significantly vulnerable cohort. No after-care support program to date has been completely informed by young people and their care team. This scoping study explored the perspectives of young people and their wider care team on: (1) challenges surrounding the transition process; and (2) how these challenges can be addressed. Semi-structured interviews and focus group sessions were conducted with 33 stakeholders from OoHC (i.e., young people in care; young people who had transitioned from care; carers; caseworkers and senior OoHC executives). Four themes captured the challenges of transitioning out of care, including: (1) inadequate processes underpinning the transition; (2) instability within the family unit; (3) financial challenges and (4) lack of independence during care. Stakeholders agreed that greater support during the transition process is necessary, including life-skills training while in care and a post-care worker and/or mentor to provide after-care support. These findings provide compelling insights into the challenges that young people transitioning from OoHC experience and possible solutions for how such challenges can be addressed. These findings will inform the development and delivery of a co-designed and specialised after-care support service for this population.